SCORE AS ELEMENT METHOD OF ACCOUNTING - Vasilieva, L.N.; Bondarchuk , N.V. (The actual problems of regional economy development, 2016)
The article investigated the concept of evaluation is fundamental to the economy, especially in today's market conditions. Assessment, along with elements such as documentation, inventory, accounts and double entry, balance and reporting forms method of accounting. It stated that the elements of the method of accounting in relation to the assessment can be classified according to the following criteria: those that affect the valuation, namely documentation and inventory; those that are under the influence of assessment, namely: accounts and double entry, balance sheet and statements. JEL: M41